First-principles prediction on geometrical and electronic properties of K-doped chrysene. (May 2017) - Wang, Xiaohui; Zhong, Guohua; Yan, Xunwang; Chen, Xiaojia; Lin, Haiqing
Abstract: The significant discovery of superconductivity in potassium (K) doped polycyclic aromatic hydrocarbons (PAHs) provides a novel system to understand the superconducting mechanism. Here, we focus on K-doped chrysene which is possibly a superconductor. Chrysene contains four benzene rings, however, the superconductivity induced by the K doping has not been discovered. Based on the first-principles calculations with the Van der Waals functional correction, we predicted the geometrical and the electronic structures of K x -doped chrysene ( x =1, 2, 3 and 4). We found that the K doping results in the phase transition from C 2/ c to P 21 symmetry. The result of the formation energies shows that K2 -doped chrysene is the most stable and can easily be fabricated. K2 chrysene is still a semiconductor, but K2 chrysene with small charge fluctuation can behave as a metal and is thermodynamically stable. Our results provide a route to experimentally obtain the stable K-doped chrysene with metallic feature. Highlights: The K doping results in the phase transition from C 2/ c to P 21 . K2 chrysene is the most stable and is easily fabricated. K2 chrysene with small charge fluctuation is metallic and is thermodynamically stable.